Salt resistance of interspecific crosses of domesticated and wild rice species - Wairich, Andriele; Wember, Louisa Sophie; Gassama, Lamin J.; Wu, Lin-Bo; Murugaiyan, Varunseelan; Ricachenevsky, Felipe Klein; Margis-Pinheiro, Marcia; Frei, Michael (Wiley, 2021)
alt stress negatively affects rice growth and yield in many parts of the world. Cultivated rice (Oryza sativa L.) is very sensitive to salt stress. Breeding attempts to develop salinity‐adapted rice varieties have been hampered by the quantitative nature of adaptation and limited genetic variability in cultivated rice.AimsWe aimed to explore the potential of wild rice species for improving adaptation to salinity. We screened two populations of introgression lines (ILs) derived from crosses between O. sativa (cv. Curinga) × O. meridionalis (CM population) and between O. sativa (cv. Curinga) × O. rufipogon (CR population) to identify quantitative trait loci (QTLs) and associated resistance mechanisms to salt stress.MethodsWe used previously developed ILs and screened them for adaptation to salt stress. In addition, we performed physiological, biochemical, and mineral analysis with the most resistant ILs identified for each population.ResultsThree and 19 QTLs for different vegetation indices were identified for the CM and CR population, respectively. We identified two ILs with superior resistance to salinity. These ILs showed enhanced vegetation indexes and maintained relatively high gas exchange under salt stress. In addition, these ILs showed less damage to cell membranes and reduced formation of H2O2, when compared with the recurrent parent, O. sativa.ConclusionOur study demonstrated that rice wild relatives are promising sources of salinity resistance. Introgressions of O. meridionalis and O. rufipogon into the O. sativa genome can confer increased resistance to salinity excess.